Prevalence of pulmonary tuberculosis among the suspected patients visiting Sagarmatha Zonal Hospital, Rajbiraj. - Mali, Siyaram Bhagat (2012)
ABSTRACT: Tuberculosis is an infectious disease caused by the bacillus Mycobacterium tuberculosis. It typically affects the lungs (pulmonary tuberculosis) but can affect other sites as well (extra pulmonary tuberculosis). The disease is spread in the air when people who are sick with pulmonary TB expel bacteria, for example by coughing. The aim of this study was to find out the prevalence of pulmonary tuberculosis by Ziehl-Neelsen staining and tuberculin skin test among the different age group of suspected patients visiting Sagarmatha Zonal Hospital, Rajbiraj and to evaluate the load of acid fast bacilli in treatment failure, return after default, follow up and chronic cases of pulmonary tuberculosis. In this study, out of 884 suspected patients, 113 (12.78%) showed positive result for acid fast bacilli out of which 84 (74.34%) were male while 29 (25.66%) were female. Similarly, in case of Mantoux test, out of 361 suspected patients 73 were found to be positive for acid fast bacilli out of which 54 were male and 19 female. On the basis of both tests performed, the evidence of acid fast bacilli was found to be higher in adult (20-59 years) age group patients i.e. 60% in case of ZN stain and 52% in case of Mantoux test) followed by older (60 or >60 years) age group patients (i.e. 31.8% for ZN stain and 39.7% for Mantoux test). In the study, Mantoux test showed more positive result (positivity= 20.22% and χ2= 1.564) than that of ZN staining (showed 12.78% AFB positivity and χ2 = 3.558) performed. Key words: M. tuberculosis, ZN staining, Mantoux test.